On India's experience of development planning - Patnaik, Prabhat (1998)
The problem with Indian planning lay not in its alleged `inward-orientation', resulting in a neglect of trade possibilities, but in its inability to raise adequate investable resources. The pioneers of planning had a sophisticated view of the role of comparative advantage; but they can be faulted for underestimating the problem of resource mobilisation by holding a naive theory of the State. The recent tendency towards `liberalising' the economy exposes it to the caprices of international speculators and undermines the basis of planning. Though this process is immanent in the tendency towards the globalisation of finance, an alternative agenda involving reforms of a different kind, including land reforms, which would revamp planning in India is both feasible and necessary. - Reproduced
Keywords: Development planning - India; Development planning